Role of Interleukin-18 in Host Defense against Disseminated Candida albicans Infection - Stuyt, Rogier J. L. (American Society for Microbiology, 2002)
In mice injected intravenously with Candida albicans, administration of anti-interleukin-18 (IL-18) antibodies increased the yeast load in the kidneys. There was no effect on the organ load with Candida when gamma interferon (IFN-γ)-deficient mice were treated with anti-IL-18 antibodies, suggesting that the protective effect of IL-18 is mediated through endogenous IFN-γ.